INHIBISI KOROSI BAJA RINGAN MENGGUNAKAN BAHAN ALAMI DALAM MEDIUM ASAM KLORIDA: Review - Stiadi, Yeni; Arief, Syukri; Aziz, Hermansyah; Efdi, Mai; Emriadi, E. (Jurnal Riset Kimia, 2019)
The corrosion of steel and its alloys is an important problem in industry, especially in acidic environments. Mild steel is one of the important alloys of iron which has many industrial applications because of its excellent mechanical properties, but mild steel is susceptible to corrosion. Corrosion problems need to be a concern and must be handled properly. Hydrochloric acid is widely used for pickling, cleansing, decomposition and metal etching, on the other hand also contributes to corrosion of metal surfaces. Plant extracts investigated the properties, mechanisms of adsorption and efficiency of inhibition as environmentally friendly corrosion inhibitors for various steel materials in different acidic media. The efficiency of corrosion inhibition of steel from plant extracts analyzed ranged from 72-98% and generally as a mixed-type inhibitor. Most of the inhibitors are adsorbed on the steel surface through a physisorption mechanism.